Seawater carbonate chemistry inside and outside the CO2 vent (Ischia, Italy) before and during a reciprocal transplant experiment with Platynereis spp. in September 2013 - Turner, Lucy M; Madeira, Diana; Ricevuto, Elena; Massa Gallucci, Alexia; Sommer, Ulf; Viant, Mark R; Dineshram, Ramadoss; Gambi, Maria Cristina; Calosi, Piero (PANGAEA, 2025)
Platynereis spp. were collected via snorkelling or scuba from either inside (40°43′53″N, 13°57′47″E) (stations A1-A3) or outside (40°43'33.33N, 13°57'36.38E and 40°44′48″N, 13°56′39″E) (stations C1-C3) the carbon dioxide (CO2) vent on the island of Ischia (Italy) and used in a reciprocal transplant experiment between 04/09/2013 and 16/09/2013. The effect of exposure to high or low partial pressures of CO2 (pCO2) conditions on the proteome and metabolome (metabolome, and lipidome) of worms from different pCO2 regimes was investigated to understand the effect of exposure to different pCO2 conditions on the cellular physiological response. Before and during the transplant experiment water samples were taken to characterise the physio-chemical parameters of sea water used when exposing the worms to: (i) low pCO2 conditions ('control' stations C1, C2 and C3) and (ii) high pCO2 conditions ('acidified' stations A1, A2, A3). Salinity, temperature, pH NBS (Mettler-Toledo pH meter, Beaumont Leys, UK), total alkalinity (TA) (AS-ALK2, Apollo SciTech, Bogart, USA), dissolved inorganic carbon (DIC), carbon dioxide partial pressure (pCO2), bicarbonate and carbonate ion concentration ([HCO3–] and [CO32–), calcite and aragonite saturation state (Ωcal and Ωara) are provided. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from the PANGAEA dataset (see Source). In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-11-03.
Keywords: Animalia; Annelida; Benthic animals; Benthos; CO2 vent; Coast and continental shelf; Field experiment; Mediterranean Sea; Other studied parameter or process; Platynereis sp.; Single species; Temperate